Examining the implementation of teaching and learning interactions of transition cultural competence through a qualitative study of Taiwan mentors untaking the postgraduate nursing program. (August 2019) - Chang, Li-Chun; Chiu, Ching-Wen; Hsu, Chih-Ming; Liao, Li-Ling; Lin, Hui-Ling
Abstract: Background: Cultural competency has been identified as an essential curricular element in undergraduate and graduate nursing programmes. Supporting successful transition to practice is essential for retaining graduate nurses in the workforce and meeting the demand for cultural diversity in health care services. Objectives: This study aimed to explore the teaching and learning interactions of transition cultural competence from the perspective of mentors of newly graduated nurses in a Taiwanese postgraduate nursing programme. Design: A qualitative design that utilised focus group interviews was adopted for this study. A framework approach—a content and thematic analysis strategy—was used to analyse the interviews. Setting: The study setting consisted of two hospitals in northern Taiwan. Participants: The study participants consisted of 24 new graduate nurse mentors. Methods: Three focus group sessions were conducted (two at a medical centre and one at a district hospital), where the participants were interviewed. Results: Four themes were derived from the data—transition process, teaching strategies according to the transition stage, learning after overcoming clinical stress, and awareness of cultural diversity among new graduate nurses. The clinical routine and physical stress of caring for patients did not allow the newly graduated nurses to appropriately demonstrate cultural competence in the first three months. Mentors were only able to provide resources for new graduate nurses when they first started to care for patients in cultural groups. The point of catalysis was when learners finally gained awareness of cultural differences, and, consequently, they could encounter the teaching and learning process. Conclusion: The different learning stages and teaching strategies illustrated the interactive process between new nurses and educators. Facilitating the cultural awareness of learners is a challenge for teachers who provide cultural competence training. This model could serve as a reference for curriculum and clinical training programmes.